The role of pharmacists in antimicrobial stewardship: a scoping review - Sarfo, Chennette M.; Okyere, Harry A.; Gyekye, Isaac A.; Bruce, Suliasnaia P.; Ofei-Palm, Charles; Wutor, Victor C. (International Journal Of Community Medicine And Public Health, 2026)
Antimicrobial stewardship programs optimize antimicrobial use and combat antimicrobial resistance (AMR). This scoping review examines the roles of pharmacists in antimicrobial stewardship, pharmacist-led interventions, barriers to participation, and recognition mechanisms to enhance pharmacist engagement. The study followed PRISMA methodology, searching databases for literature published between 2010 and 2023. Twenty-four studies met the inclusion criteria. The review reveals that pharmacists undertake a range of functions, including administering pharmacotherapy, monitoring therapeutic drugs, and assessing patients for optimal treatment. Effective pharmacist-led interventions include audit and feedback systems, prior authorization protocols with educational components, real-time alert technologies, and the implementation of evidence-based guidelines. However, key barriers to participation include limited access to resources, ineffective inter-professional communication, and organizational constraints. The review further reveals that recognition mechanisms identified to enhance pharmacist engagement include administrative support, increased involvement in decision-making, enhanced education, and streamlined processes. The review emphasizes the importance of individualizing antimicrobial strategies through interprofessional collaboration, expanding education, implementing clinical decision support systems, fostering an antimicrobial stewardship culture, and supporting research innovations. Addressing the identified barriers and enhancing support mechanisms will maximize pharmacists’ contributions to antimicrobial stewardship, ultimately improving patient outcomes.